Bitcoin as a virtual currency - Anna Wisniewska (Institute of Economic Research (IER), 2015)
The aim of this article is to show the position of Bitcoin among virtual currencies. On the basis of the reports published by the European Central Bank and The Financial Action Task Force, as well as the available Internet and primary sources, there have been presented the types and the history of virtual currencies, the way in which Bitcoin functions and the methods of acquiring it. The article is based on the assumption that an in-depth knowledge of virtual currencies, their classification and their functioning will make it possible to regulate their legal status. It is necessary not only for tax purposes, but also in order to avoid the risk of using this payment method for terrorist or criminal purposes. The knowledge of the history of virtual currencies also makes it possible to foresee the problems that may hinder the functioning of Bitcoin and other virtual currencies. The growing popularity of virtual currencies and cryptocurrencies is linked with the increase of importance of non-cash payments on global scale. Thus, Bitcoin may be considered a next step in the evolution of digital money.
Keywords: E40; G29; E49; 330; bitcoin; virtual currencies; cryptocurrencies